Arctic National Wildlife Refuge (ANWR): An Overview - Comay, Laura B.; Ratner, Michael; Crafton, R. Eliot (Library of Congress. Congressional Research Service., 2018)
This report discusses the oil and gas program recently approved by President Trump for the Arctic National Wildlife Refuge (ANWR) in the context of the ANWR's history, its energy and biological resources, Native interests and subsistence uses, energy market conditions, and debates over protection and development.